KERJA SAMA INDONESIA DAN UNICEF DALAM MENGATASI KEKERASAN SEKSUAL PADA ANAK BERBASIS SIBER TAHUN 2016-2020 - Rifda Vitaprilia Catarianandriya (2024)
Sexual violence against children and technological advances is possible to become a threat to a country if not strictly regulated by law. Seeing these situations, a new crime has emerged among society, namely sexual violence against children in the cyber realm. To overcome this, the Indonesian government together with UNICEF then formed a collaboration. To explain further about the collaboration between Indonesia and UNICEF, the author uses the concept of international cooperation and role theory with descriptive qualitative research methods and data collection methods using literature reviews in the form of Country Program Action Plan (CPAP) documents and Child Protection Case Data Reports. The aim of this research is to find out how cooperation is carried out by Indonesia and UNICEF in overcoming cyber-based sexual violence against children. The final results of this research found that in dealing with cases of sexual violence against children in the cyber domain, several parties were involved, including Bappenas, KOMINFO, KPAI, and the Ministry of Social Affairs. The real form of this cooperation is the formation of work programs to overcome sexual violence against children in the cyber domain according to the parties involved.